2022
DOI: 10.1051/0004-6361/202244495
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of star formation histories of AGN and non-AGN galaxies

Abstract: We use AGN with X-ray luminosities, L X,2−10keV ∼ 10 42.5−44 erg s −1 , from the COSMOS-Legacy survey that lie within the UltraVISTA region and cross match them with the LEGA-C catalogue. The latter provides measurements of the calcium break, D n 4000, and H δ Balmer line that allow us to study the stellar populations of AGN and compare them with a galaxy reference catalogue. Our samples consist of 69 AGN and 2176 non-AGN systems, within 0.6 < z < 1.3, that satisfy the same photometric selection criteria. We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 111 publications
4
18
0
Order By: Relevance
“…The CIGALE code provides stellar ages estimates. However, Mountrichas et al (2022b) caution that the CIGALE estimates have limited accuracy if they are not combined with D n and H δ measurements. Hence, they developed a variant of the CIGALE code which uses both these indices to estimate the mass weighted galaxy ages.…”
Section: Stellar Agesmentioning
confidence: 99%
See 2 more Smart Citations
“…The CIGALE code provides stellar ages estimates. However, Mountrichas et al (2022b) caution that the CIGALE estimates have limited accuracy if they are not combined with D n and H δ measurements. Hence, they developed a variant of the CIGALE code which uses both these indices to estimate the mass weighted galaxy ages.…”
Section: Stellar Agesmentioning
confidence: 99%
“…As this code is not publicly available, we can rely on their galaxy age methodology. This is possible because the LEGA-C COSMOS sample used by Mountrichas et al (2022b) is practically identical to our sample and moreover they use the same parameter grid for their SED fitting. Mountrichas et al (2022b) derive the spectral age index using both the D n and EW(H δ ) measurements.…”
Section: Stellar Agesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, in both lower mass and more massive galaxies the SFR of AGN was similar to that of non-AGN systems (Mountrichas et al 2021(Mountrichas et al , 2022c. These results were also supported by studying the stellar populations of lowto-moderate L X AGN compared to non-AGN systems (Mountrichas et al 2022b).…”
Section: Introductionmentioning
confidence: 52%
“…In Mountrichas et al (2022b), we examined the SFH of AGN and non-AGN galaxies and we found that AGN of low-to-moderate L X (log [L X,2−10keV (erg s −1 )] < 44) tend to have older stellar populations and are less likely to have experienced a recent star formation burst compared to non-AGN systems. Here, we study the SFH of the two populations, but, in addition, we take into account their cosmic environment (Sect.…”
Section: Star-formation Historymentioning
confidence: 99%